2018
DOI: 10.1111/geoj.12274
|View full text |Cite
|
Sign up to set email alerts
|

A geographical multivariable multilevel analysis of social exclusion among older people in China: Evidence from the China Longitudinal Aging Social Survey ageing study

Abstract: Social exclusion is increasingly considered to be a multi‐faceted concept involving more than simply material disadvantage among older people. The process of social exclusion may be driven by various factors and at different levels, including individual, household, group, community, country and global levels. Using data from the 2014 China Longitudinal Aging Social Survey focusing on respondents aged over 60, we employed multivariate multilevel models to simultaneously estimate four dimensions of social exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Older adults are also more likely to get emotional support from neighbours when living in neighbourhoods with higher neighbourhood social participation (Luo et al, 2012;Yang & Victor, 2008). Older adults are at high risk of suffering from loneliness and subjective feeling of exclusion (Feng, Phillips, & Jones, 2018), but neighbourhood social participation may encourage them to communicate with and comfort each other, increasing their emotional support (Luo et al, 2012;Yang & Victor, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Older adults are also more likely to get emotional support from neighbours when living in neighbourhoods with higher neighbourhood social participation (Luo et al, 2012;Yang & Victor, 2008). Older adults are at high risk of suffering from loneliness and subjective feeling of exclusion (Feng, Phillips, & Jones, 2018), but neighbourhood social participation may encourage them to communicate with and comfort each other, increasing their emotional support (Luo et al, 2012;Yang & Victor, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that while not presenting formal conceptualisations, important edited volumes on social exclusion of older people (e.g. Scharf and Keating 2012;Börsch-Supan et al 2015), seminal works on related concepts (such as cumulative advantage/disadvantage - Dannefer (2003); precarity - Grenier et al (2020)), and recent empirical/measurement papers (Dahlberg and McKee 2018;Feng et al 2018;Van Regenmortel et al 2018;Prattley et al 2020;Keogh et al 2021) have significantly expanded our conceptual understanding of multifaceted forms of disadvantage in later life.…”
Section: Conceptualising and Defining Social Exclusion Of Older Peoplementioning
confidence: 99%
“…Factors such as advanced age, lower health status, greater number of chronic conditions, lower education, not being married and smoking are also associated with the probability of institutionalization and the determinants of health of people living in the community [11]. The health of older populations is apparently not only affected by individual factors, but political economy factors such as disparities in economic development and allocation of health care resources, create health inequities among the older population [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that uneven economic development, varied social security provision as well as different family support at regional levels all contributed to the geographical variations in health outcomes of the older population [22]. Recently, Feng et al have explored regional and social differences in social exclusion of older persons in China based on the 2014 China Longitudinal Aging Social Survey (CLASS) data and the relations with health and well-being [12]. The results showed that older people with lower educational attainment, in the lowest quintile of personal income and in poor health were the most likely to be excluded.…”
Section: Introductionmentioning
confidence: 99%